2023
DOI: 10.3390/molecules28041778
|View full text |Cite
|
Sign up to set email alerts
|

A Synergetic Strategy for Brand Characterization of Colla Corii Asini (Ejiao) by LIBS and NIR Combined with Partial Least Squares Discriminant Analysis

Abstract: A synergetic strategy was proposed to address the critical issue in the brand characterization of Colla corii asini (Ejiao, CCA), a precious traditional Chinese medicine (TCM). In all brands of CCA, Dong’e Ejiao (DEEJ) is an intangible cultural heritage resource. Seventy-eight CCA samples (including forty DEEJ samples and thirty-eight samples from other different manufacturers) were detected by laser-induced breakdown spectroscopy (LIBS) and near-infrared spectroscopy (NIR). Partial least squares discriminant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…E’Jiao, also known as Colla corii asini, is a traditional Chinese medicine derived from donkey-hide gelatine [ 20 , 21 , 22 ]. Modern pharmacology studies demonstrated that E’Jiao could significantly increase haematopoietic stem cells, burst-forming unit-erythroid and colony-forming unit granulocyte-macrophages in the bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…E’Jiao, also known as Colla corii asini, is a traditional Chinese medicine derived from donkey-hide gelatine [ 20 , 21 , 22 ]. Modern pharmacology studies demonstrated that E’Jiao could significantly increase haematopoietic stem cells, burst-forming unit-erythroid and colony-forming unit granulocyte-macrophages in the bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…NIR spectral data could help to compensate for sample matrix variability(De Oliveira et al, 2019). In another work,Xia et al (2023) revealed the effectiveness of a synergistic strategy of data fusion, combining LIBS and NIR, for rapid identification of Colla Corii Asini (Ejiao). The researchers collected LIBS and NIR spectra of Dong'e Ejiao and observed characteristic spectral lines of Ca, Na, Mg, K, and Fe in the LIBS spectra.…”
mentioning
confidence: 99%